Emission of particulate matter during the combustion of bio-oil and its fractions under air and oxyfuel conditions - Feng, Chao; Gao, Xiangpeng; Wu, Hongwei (Combustion Institute, 2017)
© 2016.The study reports the emission of inorganic particulate matter (PM) with aerodynamic diameters <10µm (PM10) during the complete combustion of bio-oil in a drop-tube-furnace (DTF) system at 1400°C under air and two oxyfuel conditions (i.e., 21%O2/79%CO2 and 30%O2/70%CO2, by volume). Three bio-oil samples were studied, i.e., a raw bio-oil, a filtrated bio-oil (prepared from the raw bio-oil after fine char particles were removed via filtration), and the water-insoluble fraction of the filtrated bio-oil (blended with ethanol). The total inorganic species of the raw bio-oil are distributed dominantly (74.7%) in the water-soluble fraction but minorly in the water-insoluble fraction (10.4%) and suspended fine char particles (14.9%). The results from the combustion experiments show that the PSDs of PM10 from the complete combustion of the raw and filtrated bio-oils have a bimodal distribution, with a fine mode at ~0.03µm and a coarse mode at ~2.0µm. The water-insoluble fraction and the fine char particles suspended in the raw bio-oil have insignificant contributions to PM10 emission during the combustion of the raw bio-oil. It is the water-soluble fraction that plays a key role in the emission of PM10 during the combustion of the raw bio-oil. The data also show that PM10 emission during the complete combustion of bio-oil is insensitive to combustion atmosphere (air or oxyfuel) because complete bio-oil combustion is dominated by gaseous-phase reactions and the contribution of solid combustion is minimal. However, the excessive CO2 under oxyfuel conditions leads to more Fe being partitioned into PM0.1-1.